2019
DOI: 10.1186/s40814-019-0469-7
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of foot orthoses in individuals with patellofemoral osteoarthritis: a randomised feasibility trial

Abstract: Background Foot orthoses have the potential to be an efficacious treatment for patellofemoral osteoarthritis (PFOA) but have not been evaluated in clinical trials in this population. This study aimed to determine the: (i) feasibility of conducting a randomised controlled trial (RCT) investigating the efficacy of foot orthoses in individuals with PFOA; and (ii) effects of foot orthoses versus flat shoe inserts on pain, function, and knee-related quality of life (QOL). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 45 publications
1
36
2
Order By: Relevance
“…addressing greater midfoot flexibility) [ 51 ]. This is supported by previous studies that have demonstrated that individuals with PFOA respond favourably to foot orthoses and/or footwear immediately [ 44 , 52 ], and in the short-term (6 weeks) [ 46 ]. However, future trials are now required to determine if such interventions are effective in isolation versus being a part of a multimodal treatment plan.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…addressing greater midfoot flexibility) [ 51 ]. This is supported by previous studies that have demonstrated that individuals with PFOA respond favourably to foot orthoses and/or footwear immediately [ 44 , 52 ], and in the short-term (6 weeks) [ 46 ]. However, future trials are now required to determine if such interventions are effective in isolation versus being a part of a multimodal treatment plan.…”
Section: Discussionsupporting
confidence: 83%
“…Higher FPI (indicative of a more pronated foot posture) was significantly associated with fewer repeated single step-ups and double-leg sit-to-stands to knee pain onset. Foot pronation has previously been highlighted as being associated with PFP [ 13 , 15 ] and may therefore influence the efficacy of in-shoe interventions in this population [ 43 ], with recent studies providing preliminary evidence that foot orthoses may be an effective treatment in individuals PFOA [ 44 46 ]. One of the proposed mechanisms is that foot pronation, leading to internal tibial and femoral rotation, causes either a decrease in PFJ contact area or an increase in PFJ reaction forces, thereby elevating PFJ loads [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies ([ 14 ] (n=30) [ 15 ]; (n=106)) assessed some of the participants from a parent trial ([ 13 ], n=126). Tan et al [ 23 ] was a biomechanical study nested within a pilot RCT [ 22 ]. Two studies did not provide information on the sex of the participants (Kumar & Ganesh 2011 [ 20 ];), so excluding these, the overall percentage of females (62%) was greater than males though there was wide variation in the proportion of males and females between the studies (males 14–45% and females 55–86%).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of 27 was not formally determined. It was based on previous pilot RCTs evaluating health-professional guided interventions for musculoskeletal conditions (41,67), and deemed su cient to assess the feasibility criteria. Participants who completed baseline and follow-up evaluations were included in the analysis, as recommended in the CONSORT guidelines (48).…”
Section: Discussionmentioning
confidence: 99%